Question not found

Not a good answer? Get an answer now. (Free)

Rating

There are no new answers.

Evaluate the expression for the given value of the variable(s).
-x2 - 4x; x = –3
A. 3
B. –1
C. 11
D. –17 **Weegy:** -x^2 - 4x= A. 3 when x= -3 **User:** Combine like terms. What is a simpler form of the expression?
-3(-4y + 3) + 7y
A. 19y - 9
B. 10y
C. -19y + 3
D. -19y - 9
**Weegy:** The answer for -3(-4y + 3) + 7y is 19y - 9. (More)

Question

Expert Answered

Asked 1/21/2013 12:34:57 PM

0 Answers/Comments

What is the expression in factored form?
x2 + 14x + 48
A. (x + 6)(x - 8)
B. (x + 8)(x - 6)
C. (x - 8)(x - 6)
D. (x + 6)(x + 8) **Weegy:** D. (x + 6)(x + 8) is the answer. **User:** Simplify the expression.
(3 + i) - (2 - 2i)
A. 1 + 3i
B. 5 - i
C. 4i
D. -1 - 3i **Weegy:** B. 5 - i **User:** The function y = 16t2 + 486 models the height y in feet of a stone t seconds after it is dropped from the edge of a vertical cliff. How long will it take the stone to hit the ground? Round to the nearest hundredth of a second.
A. 7.79 seconds
B. 11.02 seconds
C. 0.25 seconds
D. 5.51 seconds **Weegy:** The answer is 5.51 seconds
**User:** What is the expression in factored form?
16x2 - 25
A. (4x - 5)2
B. (4x + 5)(-4x - 5)
C. (4x + 5)(4x - 5)
D. (-4x + 5)(4x - 5) **User:** What value completes the square for the expression?
x2 - 18x
A. 9
B. -9
C. 81
D. -81 **Weegy:** C. 81 completes the square for the expression. **User:** What is the expression in factored form?
9x2 - 12x + 4
A. (-3x - 2)2
B. (-3x + 2)(3x - 2)
C. (3x - 2)2
D. (3x + 2)2 **Weegy:** C. (3x - 2)2. I assume you mean 9x^2 - 12x + 4. **User:** The function h = -t2 + 95 models the path of a ball thrown by a boy where h represents height, in feet, and t represents the time, in seconds, that the ball is in the air. Assuming the boy lives at sea level where h = 0 ft, which is a likely place the boy could have been standing when he threw this ball?
A. his backyard
B. an underground cave
C. a ladder
D. a bridge **Weegy:** B. an underground cave. He is currently situated below sea level. Source: **User:** Solve the equation.
x2 + 18x + 81 = 25
A. 14, 4
B. –4, –14
C. 14, –14
D. –4, 4 **Weegy:** C. 81 completes the square for the expression. **User:** What is the equation, in standard form, of a parabola that models the values in the table?
x -2 0 4
f(x) -7 3 -73
A. y = -3x2 - 3x + 4
B. y = 4x2 + 3x - 3
C. y = -4x2 - 3x + 3
D. y = -3x2 - 4x + 3 **Weegy:** D. y = -3x^2 - 4x + 3
is the answer. **User:** Use the Quadratic Formula to solve the equation.
-2x2 - 5x + 5 = 0 **Weegy:** 0. A. **User:** What is the fourth term of (d + ... (More)

Question

Not Answered

Updated 271 days ago|6/3/2014 11:18:48 PM

5 Answers/Comments

(3 + i) - (2 - 2i)

= 3 + i - 2 + 2i

= 1 + 3i

= 3 + i - 2 + 2i

= 1 + 3i

Added 271 days ago|6/3/2014 11:05:48 PM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by yumdrea [6/3/2014 11:09:50 PM]

x^2 + 18x + 81 = 25

x^2 + 18x + 81 - 25 = 0

x^2 + 18x + 56 = 0

(x + 4)(x + 14) = 0

x = -4 or x = -14

x^2 + 18x + 81 - 25 = 0

x^2 + 18x + 56 = 0

(x + 4)(x + 14) = 0

x = -4 or x = -14

Added 271 days ago|6/3/2014 11:07:05 PM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by yumdrea [6/3/2014 11:09:27 PM]

[Deleted]

Added 271 days ago|6/3/2014 11:08:49 PM

-x^3 + 5x^2 - 11x + 55 = 0

-x^2(x - 5) - 11(x - 5) = 0

(x - 5)(-x^2 - 11) = 0

x - 5 = 0 or -x^2 - 11 = 0

x = 5 or x = ± (sqrt 11)i

-x^2(x - 5) - 11(x - 5) = 0

(x - 5)(-x^2 - 11) = 0

x - 5 = 0 or -x^2 - 11 = 0

x = 5 or x = ± (sqrt 11)i

Added 271 days ago|6/3/2014 11:11:12 PM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by andrewpallarca [6/4/2014 12:58:23 PM]

x^3 - 2x^2 + 10x + 136 = 0

(x + 4)(x^2 - 6x + 34) = 0

x + 4 = 0 or x^2 - 6x + 34 = 0

When x + 4 = 0, x = -4

When x^2 - 6x + 34 = 0

x = [6 ± sqrt (-100)]/2 = (6 ± 10i)/2 = 3 ± 5i

The solution is {-4, 3 + 5i, 3 - 5i)

(x + 4)(x^2 - 6x + 34) = 0

x + 4 = 0 or x^2 - 6x + 34 = 0

When x + 4 = 0, x = -4

When x^2 - 6x + 34 = 0

x = [6 ± sqrt (-100)]/2 = (6 ± 10i)/2 = 3 ± 5i

The solution is {-4, 3 + 5i, 3 - 5i)

Added 271 days ago|6/3/2014 11:18:48 PM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by andrewpallarca [6/4/2014 12:58:51 PM]

19,737,199 questions answered

Points 0 [Total 0]| Ratings 0| Comments 0| Invitations 0|Offline

Points 0 [Total 0]| Ratings 0| Comments 0| Invitations 0|Offline

There are no comments.